Systematic Literature Review: Analysis of the Use of Website-Based Physics Learning Devices to Support Students' Abilities in Learning Physics in High Schools - Simon Karuku (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: This study aims to determine students' abilities with the use of web-based physics teaching materials at the high school level. Methodology:This research is a qualitative research with a systematic literature review research method. The population in this study were 55 articles obtained from Google Scholar with publications ranging from 2017 to 2022. Meanwhile, the sample in this study were 10 articles related to the title of this study. Main Findings: Through the analysis and review of the articles carried out, it can be seen that website-based physics teaching materials are a form of innovation that teachers can use to support physics learning. The use of website-based physics teaching materials can support the ability to think creatively, independent learning, scientific literacy skills, learning outcomes, and competency achievement. Novelty/Originality of this study: The novelty of this research is the discovery of an innovation for educators in achieving learning objectives and supporting students' abilities, namely through the use of website-based physics teaching materials in high school physics learning which is a good innovation used to help teachers achieve learning goals and support students' abilities.